CUSTOMERS' SATISFACTION ON HOTEL INTERNET SERVICE IN SINGAPORE: AN EXPLORATORY STUDY - NG, KEITH (ITB Journal Publisher, LPPM ITB, 2008)
Advances in the development of internet technologies have created new avenues for the hotel industry; however embracing internet technologies does not necessitate the success of any hoteliers. From a customer perspective, ability to access more information meant that service providers such as hoteliers need to meet increasing demands to fulfill expectations. It is imperative that the hotel industry must constantly adapt to environment changes such as meeting the demands of customers utilizing innovative technology. While most hoteliers would agree that using the Internet creates benefits for the customers, little is known about the mechanisms in generating customer satisfaction on the Internet. This study will explore the reasons that influenced Internet users ' satisfaction in the hotel industry and identify new directions of the Internet for the hotel industry.